Silicon and plant diseases. a review (2011)
Disease is one of the main limitations on the amount and quality of crop production, by reducing the availability, absorption, distribution and use of nutrients by the plant. Silicon (Si) is one of the most abundant elements in the lithosphere and most soils have considerable amounts. Although not considered an essential nutrient for most plants, a lot of evidence shows the beneficial effects of nutrition with Si on growth, development and health of crops. Many studies have suggested that Si activates the defense mechanisms of plants, but the exact nature of the interaction between this element and the biochemical pathways that direct resistance still remains unclear. This article presents a review of the relationship between mineral nutrition and disease development and discusses the beneficial effects of silicon in crops, its mobility in soil, the process of assimilation through the roots and its influence on tolerance to fungal diseases.